Milk production in Finnsheep and Romanov breeds - Boylan, W. J.; Sakul, H. (Agricultural and Food Science, 1988)
The Finn, Romanov and several U.S. sheep breeds were machine milked to obtain information on several measures of milk production and milk composition. Data were obtained over at wo year to four year period utilizing 146 purebred ewe records and 165 crossbred ewe records. The level of milk production for a 130 day lactation period for the breeds evaluated was generally low compared to traditional European dairy breeds. The least-squares overall mean for milk yield was 68.8 liters. The Suffolk (80.5 liters) and the Rambouillet (75.3 liters) were superior. The Targhee, Dorset and Lincoln breeds followed in order for milk yield. The Finn (64.0 liters) and Romanov (39.1 liters) were lowest. Finn sired crossbred ewes had the highest level of milk production (84.4 liters) in a four breed diallel mating design of Finn, Dorset, Lincoln and Rambouillet breeds. A value of 15.4 % was found for heterosis in milk production.